Surgical Site Infection (Ssi) In Open Vs Laparoscopic Appendicectomy In Case Of Complicated Appendicities: A Retrospective Study - Bhuiyan, Md Nur Hossain; Nahid, Sayed Md Samser; Afrose, Rumana; Ali, SM Ashraf; Yusuf, Omar Faruque; Nizamuddin, Md (Journal of Chittagong Medical College Teachers’ Association, 2013)
Appendicectomy is one of the most common surgical procedures in day to day practice in Bangladesh. Although it is considered a safe operation, a potential complication developed in complicated appendicitis. Surgical site infection is one of those noticeable complications. Infection of wound still remains one of the main postoperative morbidities and as a result, prolonged hospitalization in those undergoing open appendicectomy(OA).Laparoscopic appendectomy (LA) has been widely practiced for uncomplicated appendicitis. The role of laparoscopy in management of complicated appendicitis remains undefined. Complicated appendicitis is associated with a significant risk of postoperative morbidity, making the value of the minimally invasive approach is superior. This is a retrospective study comparing SSI in laparoscopic appendicectomy versus open appendicectomy. The study was performed on 120 patients which were clinically and after investigation diagnosed as a case of complicated appendicitis from January 2008 to June 2011. Out of them 60 patient were done by laparoscopically and 60 patients by open method. Complicated appendicitis includes perforated appendicitis, gangrenous appendicitis and appendicular abscess or early lump found intra-operatively. Patients were excluded if the diagnosis of appendicitis was not clinically established and if they had a history of symptoms for more than 5 days and/or a palpable mass in the right lower quadrant. The conversion rate, operative time, SSI (postoperative abdominal and wound infections), the return to oral intake, and the length of hospitalization were analyzed .The aim of this study is to compare the SSI between LA and OA for complicated appendicitis. In 60 patients of laparoscopic appendectomy for complicated appendicitis there were 35 patients with perforated appendicitis, 12 patients with gangrenous appendicitis and 13 patients with early appendicular lump or abscess. There were 42 males and 18 females, mean age 24 yrs (range, 18 to 32), The average operating time was 65 minutes. The average length of hospitalization was 3.2(2-5) days. The post operative narcotic analgesic requirement was minimal. Laparoscopy was converted to open surgery in two patients (3.33%). Four (6.6%) had post operative complications (diarrhea). Nine patients developed (15.00%) developed wound (port) infection. SSI . No statistically significant differences in operative time (P0.13) There was no mortality in the current series. Laparoscopic appendectomy is a safe and feasible treatment option in complicated appendicitis. It is advantageous than open surgery because of less wound infection, less morbidity, less hospital stay and early return to work and not associated with increased risk of septic postoperative complications. JCMCTA 2013; 24 (1):53-57